Growth and yield performance of oyster mushroom (Pleurotus florida) on different agricultural waste - jha, Ajit kumar; M S Behera; Sitangshu Sarkar (Mushroom Research, 2024)
The present study was conducted to evaluate different substrates for establishment of yield performance of oyster mushroom (Pleurotus florida).Oyster mushroom (Pleurotus florida) can grow on wheat straw, paddy straw, maize straw, mung straw, urd straw, arhar straw, sesamum straw, mustard straw, jute straw, mesta straw, sunhemp straw and sisal toe fibre with varying growth performances. The time required for maturing the fruiting bodies was less on wheat straw (24.1 days) followed by paddy straw (26.4 days). It was observed that the weight of fruiting bodies significantly higher in the substrate of mung straw (13.2 g/ fruit) followed by paddy straw (12.7 g/ fruit) and wheat straw (12.4 g/ fruit). The highest yield of 767.5 g/kg dry substrate with 76.8 % BE was recoded in wheat straw followed by paddy straw (747.5 g/kg dry substrate, 74.8 % BE) which was significantly superior than other substrates used. Wheat straw followed by paddy straw was identified as suitable substrates for oyster mushroom cultivation.